Clinical Staphylococcus argenteus Develops to Small Colony Variants to Promote Persistent Infection - Jiang, Bei; You, Bo; Tan, Li; Yu, Shengpeng; Li, Han; Bai, Guoqing; Li, Shu; Rao, Xiancai; Xie, Zhao; Shi, Xianming; Peng, Yizhi; Hu, Xiaomei (Frontiers in Microbiology, 2018)
Staphylococcus argenteus is a novel staphylococcal species (also considered as a part of Staphylococcus aureus complex) that is infrequently reported on, and clinical S. argenteus infections are largely unstudied. Here, we report a persistent and recurrent hip joint infection case in which a S. argenteus strain and its small colony variants (SCVs) strain were successively isolated. We present features of the two S. argenteus strains and case details of their pathogenicity, explore factors that induce S. argenteus SCVs formation in the course of anti-infection therapy, and reveal potential genetic mechanisms for S. argenteus SCVs formation. S. argenteus strains were identified using phenotypic and genotypic methods. The S. argenteus strain XNO62 and SCV strain XNO106 were characterized using different models. S. argenteus SCVs were induced by the administration of amikacin and by chronic infection course based on the clinical case details. The genomes of both strains were sequenced and aligned in a pair-wise fashion using Mauve. The case details gave us important insights on the characteristics and therapeutic strategies for infections caused by S. argenteus and its SCVs. We found that strain XNO62 and SCV strain XNO106 are genetically-related sequential clones, but the SCV strain exhibits reduced virulence but enhanced intracellular persistence compared to strain XNO62, thus promoting persistent infection. The induction experiments for S. argenteus SCVs demonstrated that high concentrations of amikacin greatly induce S. argenteus XNO62 to form SCVs, while a chronic infection of S. argenteus XNO62 slightly induces SCVs formation. Potential genetic mechanisms for S. argenteus SCVs formation were revealed and discussed based on genomic alignments. In conclusion, we report the first case of infection caused by S. argenteus and its SCVs strain. More attention should be paid to infections caused by S. argenteus and its SCVs, as they constitute a challenge to current therapeutic strategies. The problem of S. argenteus SCVs should be noticed, in particular when amikacin is used or in the case of a chronic S. argenteus infection.